Take or Wait? Learning Turn-Taking from Multiparty Data - Leite, Iolanda; Hajishirzi, Hannaneh; Andrist, Sean; Lehman, Jill (AAAI Conference on Artificial Intelligence (Late-Breaking Developments), 2013)
We build turn-taking models for autonomous characters in language-based interactions with small groups of children. Two models explore the use of support vector machines given the same multimodal features, but different methods for collecting turn-taking labels.